2017
DOI: 10.3389/fimmu.2017.00788
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Early-Life Gut Microbial Colonization during Human Immune Development: An Ecological Perspective

Abstract: Alterations in gut microbial colonization during early life have been reported in infants that later developed asthma, allergies, type 1 diabetes, as well as in inflammatory bowel disease patients, previous to disease flares. Mechanistic studies in animal models have established that microbial alterations influence disease pathogenesis via changes in immune system maturation. Strong evidence points to the presence of a window of opportunity in early life, during which changes in gut microbial colonization can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 178 publications
(211 reference statements)
1
121
0
3
Order By: Relevance
“…Microbial factors have a strong impact on the development of immune cells, including CD8 + T cells, B cells, invariant natural killer T (iNKT) cells and γδ T cells . In addition to the neonatal microbiome, antigens encountered by the future mother, such as allergens, may also influence the immune status of the offspring by potentially modulating their T‐cell maturation . In fact, previous reports have demonstrated that maternal allergen immunization prevents neonatal allergy development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial factors have a strong impact on the development of immune cells, including CD8 + T cells, B cells, invariant natural killer T (iNKT) cells and γδ T cells . In addition to the neonatal microbiome, antigens encountered by the future mother, such as allergens, may also influence the immune status of the offspring by potentially modulating their T‐cell maturation . In fact, previous reports have demonstrated that maternal allergen immunization prevents neonatal allergy development .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In addition to the neonatal microbiome, antigens encountered by the future mother, such as allergens, may also influence the immune status of the offspring by potentially modulating their T-cell maturation. 10,11 In fact, previous reports have demonstrated that maternal allergen immunization prevents neonatal allergy development. [12][13][14][15][16] Several hypotheses exist to explain the impaired allergic responses of offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, invasive F. nucleatum is persistently associated with distant metastases from primary colorectal cancers [45]. In contrast, the members of Bifidobacterium genus have been considered to inhibit colorectal carcinogenesis through the prevention of enteropathogenic infection and the inhibition of secondary bile acid production [46][47][48]. Our previous population-based study has shown that intratumoural Bifidobacterium genus may reflect loss of intestinal barrier function in poorly differentiated colorectal cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher microbial endotoxin exposure from farm animals was associated with protection against development of allergy, as suggested in the ‘Eat Dirt’ article by Weiss . Finally, because the gut microbiome is important for the prenatal–early‐life maturation of our immune system , it has been intensively studied in relation to allergic diseases, and perturbations in the infant gut microbiome have been linked to the risk of developing AD . However, several probiotic and prebiotic intervention trials have been conducted, and although some protective effect against AD was observed, the differences were small, and no clear gut microbiome–AD association could be demonstrated .…”
Section: From Disease Understanding To Biomarkers Endotypes and Tarmentioning
confidence: 99%